A sintonia entre o sindicalismo docente universitário de matriz gerencial e lobista e o paradigma da excelência: a experiência da UFMG (2003-2016) - Andressa de Araújo Moreira (2020)
The present research is located within the field of public higher education and sought to analyze, under the Marxist framework, the professors’ union fight at a university of excellence, the Federal University of Minas Gerais (UFMG), from 2003 to 2016. The central issue was to learn how professors at UFMG, a university of Brazilian excellence, relate to the union struggle and its union, the Association of University Teachers of Belo Horizonte (APUBH). To this end, it was held a bibliographical review, a documentary research with emphasis on union documents, and semi-structured interviews with UFMG professors were carried out. In regard to the Brazilian case scenario, a research of excellence and, therefore, the one which produces knowledge-merchandise, happens in state and public universities whose spreading center is concentrated in Graduate Studies. The demand that professors need to be productive adds challenges to the university professors’ union. This research has revealed that from the political role played in local and national fights, APUBH started to lead dispersive movements within the professors’ union. Under the governments of the Worker’s Party (Partido dos Trabalhadores, PT), the political group that remained in APUBH for over 10 years shifted the practice of the entity from combativeness to lobbying. At the head of the union, the board of directors has isolated the UFMG professors’ union from the entities and national teaching unionism, adopting the strategy of managing and judicializing the conflict and the professors’ rights in a particular way. The adaptation to the State has brought to the direction of APUBH a managerial conception characterized by the search for efficiency in the provision of services. This phenomenon has found a fertile environment at the university of excellence. The professors interviewed do not contradict, nor even in daily life, the induction of metrics in their work, although they defend the public and free university features. In addition to assigning union activity to "unionists", the majority of the respondents did not identify the salary adjustment nationally pleaded as a priority, due to the wage reality of the Brazilian workers. They prefer negotiating with State managers to strike practices. Under PT governments, unionism and the professors’ union struggle at UFMG are marked by class collaboration and the adherence to models of union capitalism and academic capitalism. A political and ideological conformation that favored the project of the ruling class.